The role of poverty reduction strategies in advancing economic and social rights: Malawian and Ugandan experiences - Wairama, Baker G. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.